The Prevelance of Heart Disease at Rantau Prapat Hospital, North Sumatra - Shazni Nadia Reivana; Kartika Kaban; Farida Hanum Margolang; Husnah Husnah; Sakdiah Sakdiah (Asian Journal of Natural Sciences, 2026)
Cardiovascular disease remains one of the leading causes of death worldwide, with approximately 58% of total deaths occurring in Asia. The majority of deaths are caused by ischemic heart disease (CHD) 47% or stroke 40%. The mortality rate from cardiovascular disease is projected to icrease by 91,2% by 2050 with high systolic blood preassure being the main risk factor. A descriptive cross-sectional study was conducted using medical record data of patients who visited the cardiology outpatient clinic at Rantau Prapat Regional Hospital North Sumatra between January 1 to December 31, 2023. Data collected included patient age, sex, and diagnosis. Univariate analysis was performed to describe the frequency distribution of demographic and clinical variables. A total of 2116 met the inclution criteria. The majority presented cardiac organ disorders 70.04%, followed by coronary and peripheral vascular diseases 29.63%.